Internet of Things (IoT): Definitions, Components, Characteristics and Applications - Gowda, V. Dankan; Bandaru, Venkata Naga Rani; Begum, A. Yasmine; Palanikkumar, D.; Chandrakant Jadhav, Amol (Current Overview on Science and Technology Research Vol. 8, 2022)
The Internet of Things (IoT) is a system that connects all physical devices to the web through switches, allowing them to exchange data. Web application development is advancing at a steady pace, and it is being used by a broad range of people in a variety of different fields and situations. To save human effort and make things easier, IoT often allows remote access to the existing system, which has been put up by different calculating institutions. Programed control of any gadget to get to the framework without human mediation is a unique IoT characteristic termed IoT. IoT, or the Internet of Things, refers to 'things' as a mixture of equipment components, programming information, and provided services. This device collects data from various devices from previous technological advances and exchanges it with other connected devices. IoT innovation can be portrayed as 'Web of Things', wherein this innovation is constructed dependent on the idea that all the ideal gadgets can be associated inside a particular system for sharing information and data with no manual intercession. The gadgets utilized for this can be isolated contingent to their capacity to send, get, and assemble information in the given system. IoT is obvious because of its remarkable properties that are, secure in nature, can be utilized on savvy gadgets, the capacity to interface with a system helps for the quicker network, etc. Thus IoT is a specialty innovation where heaps of work are going on and where the associations are attempting to computerize human exertion so the possibility of mistake will be negligible or zero. IoT will make things significantly simpler for people and associations with their machines to machine collaboration and network.